Change in maximal fat oxidation in response to different regimes of periodized high-intensity interval training (HIIT) - Astorino, T. A.; Edmunds, R. M.; Clark, A.; Gallant, R.; King, L.; Ordille, G. M.; Heath, B.; Montell, M.; Bandong, J. (European Journal of Applied Physiology, 2017)
Purpose: Increased capacity for fat oxidation (FatOx) is demonstrated in response to chronic endurance training as well as high-intensity interval training (HIIT). This study examined changes in maximal fat oxidation (MFO) in response to 20 sessions of periodized HIIT in an attempt to identify if various regimes of HIIT similarly augment capacity for FatOx. Methods: Thirty-nine habitually active men and women (mean age and VO2max = 22.5 ± 4.4 year and 40.0 ± 5.6 mL/kg/min) completed training and 32 men and women with similar physical activity and fitness level served as non-exercising controls (CON). Training consisted of ten sessions of progressive low-volume HIIT on the cycle ergometer after which participants completed an additional ten sessions of sprint interval training (SIT), high-volume HIIT, or periodized HIIT, whose assignment was randomized. Before and throughout training, MFO, FatOx, and carbohydrate oxidation (CHOOx) were assessed during progressive cycling to exhaustion. Results: Compared to CON, there was no effect of HIIT on MFO (p = 0.11). Small increases (p = 0.03) in FatOx were evident in response to HIIT leading to an additional 4.3 g of fat oxidized, although this value may not be clinically meaningful. Conclusions: Our results refute the widely reported increases in capacity for FatOx demonstrated with HIIT, which is likely due to marked day-to-day variability in determinations of MFO and exercise fat oxidation as well as the heterogeneity of our sample.